2018
DOI: 10.1109/toh.2018.2855175
|View full text |Cite
|
Sign up to set email alerts
|

Toward Haptic Communication: Tactile Alphabets Based on Fingertip Skin Stretch

Abstract: Abstract-This paper studies the possibility to convey information using tactile stimulation on fingertips. We designed and evaluated three tactile alphabets which are rendered by stretching the skin of the index's fingertip: (1) a Morse-like alphabet, (2) a symbolic alphabet using two successive dashes, and (3) a display of Roman letters based on the Unistrokes alphabet. All three alphabets (26 letters each) were evaluated through a user study in terms of recognition rate, intuitiveness and learnability. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…After applying the scoring template, the final similarity score is obtained. Some scholars have tried to verify the validity and reliability [41]. After reviewing the factors that affect the scoring and the current methods that mainly focus on the spoken language scoring, a method for objective scoring of the spoken language was proposed [42].…”
Section: 3mentioning
confidence: 99%
“…After applying the scoring template, the final similarity score is obtained. Some scholars have tried to verify the validity and reliability [41]. After reviewing the factors that affect the scoring and the current methods that mainly focus on the spoken language scoring, a method for objective scoring of the spoken language was proposed [42].…”
Section: 3mentioning
confidence: 99%
“…There are several ways to display tactile Morse code. The most commonly used way of displaying tactile Morse code is with vibration (see, for instance, References [14,[16][17][18]), but it can also been done using proprioceptive information by manipulating the height of a finger [17], skin stretch on the finger tip [7], or via embossed images [9]. In a direct comparison by Tan and colleagues, it was found that vibrotactile Morse led to better performance than proprioceptively presented Morse code [17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of tactile force sensors is very versatile. There are also studies on using tactile sensors to recognize alphabets such as Morse Code and Braille [110], and also using reinforcement learning for a robot to type on a Braille keyboard [111].…”
Section: Tactile Force Sensorsmentioning
confidence: 99%